Process Capability Improvement Through DMAIC Method for Aluminium Alloy Wheels Casting - Maryani, Edna; Purba, Humiras Hardi; Sunadi, Sunadi (AGUSPATI Research Institute, 2020)
High competition in the global wheel market demands is triggering the companies who are produced to improve their process to be able to offer the best wheels quality. Process monitoring charts are employed for improving the process capability index of the process, some industries set a Cp value greater than 1.33 in assessing their process capability. The aims of this research is to reduce the number of defects in the casting process using the Define Measure Analyze Improve Control (DMAIC) method. It shows the systematic way to find out the major problem root cause at the aluminum castings by using the defect diagnostic approaches and also cause and effect diagram. Other quality tools are used such as the Fishbone diagram and Pareto diagram. These tools identified the major defects for the rejections during production were identified are leaking, porosity hole motive, and oval. In determining the proposed quality improvements using the FMEA tool. The results of data processing on the calculation of process capabilities and product performance show improvements after quality improvements in the casting process.product performance was increased from Cp = 0.81 to Cp = 1.4, sigma level = 2.9 to sigma level = 4.0. The impact for the company is the defect rate was going down and finally it created the production costs saving by IDR 417,550,000 a month. Therefore, the application of the DMAIC method can provide a significant improvement in product quality and giving an impact on production cost savings